Diabetic foot. Findings on MR Imaging - Vega González, Maria Luisa; Moreno Casado, María José; Martín Peinador, Alicia (Revista Internacional de Ciencias Podológicas, 2010)
The diabetes mellitus is a systemic disease with a 5% rate of occurrence in the general population. It is cause significant morbility in the foot and ankle due to vascular disease, Neuropathy and infection. The MRI is essential to the diagnosis and evaluation of arthritis, osteomyelitis, neuropathic osteoarthropathy, cellulitis, ulcers and abscesses.
Keywords: Diabetes; MRI; Foot